(untitled) (Scotland, 1985)
Chemical and biological methods of water analysis for aquaculturalist ... Chemical sensors are in high demand for applications as varied as water pollution detection, medical diagnostics, and battlefield air analysis. Designing the next generation of sensors requires an interdisciplinary approach.
Keywords: Aquaculture,Water quality; Research,Testing